1998
DOI: 10.1116/1.581202
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic and multilayer Cr/CrN, Cr/Cr2N, and Cr2N/CrN coatings on hard and soft substrates

Abstract: Using controlled low-energy ion bombardment, CrN and Cr2N films were reactively sputtered from a Cr target in a mixed Ar-N2 discharge. Various Cr-N based coating architectures were developed in this work to provide better substrate accommodation than is currently available using monolithic CrN or Cr2N, as well as to build in “load support” for the hard surface layers on more compliant substrates. A series of monolithic and multilayer structures were deposited at low temperatures (<200 °C) to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Displayed in Figure 7 is the optimized structure compared to an empirically designed structure that has been successfully tested, 5 as well as a nonoptimal solution obtained by multiobjective optimization using GA. It was observed that the optimal solution obtained had a strain value approximately 0.5% less than one of the nonoptimal solution tested in the optimization iterations and appears to be a "better" design, in terms of the measures used here as objectives and constraints, than the most successful empirically developed coating.…”
Section: A Cr/crn Multilayer Thin Films On A2 Steel Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Displayed in Figure 7 is the optimized structure compared to an empirically designed structure that has been successfully tested, 5 as well as a nonoptimal solution obtained by multiobjective optimization using GA. It was observed that the optimal solution obtained had a strain value approximately 0.5% less than one of the nonoptimal solution tested in the optimization iterations and appears to be a "better" design, in terms of the measures used here as objectives and constraints, than the most successful empirically developed coating.…”
Section: A Cr/crn Multilayer Thin Films On A2 Steel Substratementioning
confidence: 99%
“…The past decade has seen a tremendous growth in the utilization of CrN films because of their reduced residual stress, improved oxidation resistance at high temperatures, and lower coefficients of friction when compared to TiN films. [1][2][3][4] Recently, our focus has shifted to Cr/CrN multilayer films, 5 which can be very effectively used to further improve the fracture toughness, hardness, and adhesion of these films. 6 Design of an optimal multilayer coating structure requires a detailed knowledge of the stress/strain profiles produced within the multilayer coating structure under mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…For such purposes CrN has excellent mechanical properties such as high hardness (∼28 GPa), high corrosion resistance, and excellent wear properties. [136][137][138][139][140][141][142] CrN is easy to synthesis as a thin film by magnetron sputtering (DC, pulsed DC, middle frequency RF, or High Power Impulse). [141][142][143][144][145][146][147] CrN thin films can be grown with a very low internal stresses, thus it can be synthesized in various thickness from thin to thick coatings (100 nm to 100 µm) on a variety of steels and engineering ceramics with very good adhesion.…”
Section: Review Of Chromium Nitride (Crn)mentioning
confidence: 99%
“…The results of calculation are consistent with the experimental results of the coating's optimization obtained by Kuruppu al. [21]. In turn, in [22] was optimized the geometry of multilayer TiN /TiAlN deposited on the substrate HSS (High Speed Steel) previously coated with metallic chromium.…”
Section: Introductionmentioning
confidence: 99%